Effect of vitamin C in pineapple rind (Ananas comosus L. Merr) on thyroxine hormone and anti stress on broilers in tropical region - Syahruddin E; Herawaty E; Yoki . (Jurnal Ilmu Ternak dan Veteriner, 2013)
This study was aimed to determine the right level of vitamin C in extracted pineapple rind to prevent heat stress effects so it does not interfere with the performance of broiler chickens. This study was done in a series of field experiments. Experiments in the field/cage was biological test of the effect of vitamin C from pineapple rind on production responses (percentage of body weight gain and carcass) and physiological responses (thyroxine hormone levels) in broiler chicken aged 3 weeks as many as 360 of Strain Arbor acress. The basic design used was CRD 3 x 4 factorial models and 3 replications with 10 chickens for each box, as factor 1: Room temperature (21 : 27 and 33ºC), and factor II: level of vitamin C in the pineapple rind (0:500:1000 and 1500 ppm). The data obtained were statistically analyzed using SAS program package, and if it showed any significant effect then followed by Duncans test/DMRT. Variables measured were body weight gain, carcass percentage and levels of thyroxine hormone of broiler. Results showed that addition of pineapple rind containing 500 ppm vitamin C in the drinking water reduced heat stress in chicken that were kept at temperature of 27ºC, while at 33ºC needed 1000 ppm vitamin C. Both treatments increase level of thyroxine hormone, produce weight gain equal to control, more over, there was no effect on the percentage of carcasses. Key Words: Ananas comosus L. Merr, Vitamin C, Tyrosine, Anti-Stress, Broiler Chickens